ARCHITECTURE AS A CULTURAL IDENTITY IN THE CONTINUATION OF TRADITION WITHIN MODERNIZATION - Krisprantono Krisprantono (Celt: A Journal of Culture, English Language Teaching & Literature, 2006)
The ancient and indigenous cultures that exist in the various regions of Indonesia are regarded as part of the national culture. In developing culture, Indonesia should aim at advancing civilization, culture and unity without rejecting new elements from foreign cultures that may improve or enrich the national culture and the same time raise human and Indonesian values. Architecture plays an important past in the Indonesian cultural identity. It is vital that it should be included in any plans for cultural development.